GAMBARAN KEJADIAN DIARE PADA ANAK USIA - PUTRI EKA SUDIARTI; SALMA SALMA; NIA APRILLA (Universitas Pahlawan Tuanku Tambusai, 2020)
Diarrhea is a disease that is still a health problem in developing countries, especially in Indonesia, one of them. The purpose of this study was to determine the frequency distribution and classification of diarrhea occurrences in children aged